Onion and garlic varieties - Gupta, Amar Jeet; Mahajan, Vijay; Benke, Ashwini A.; Singh, Major (Indian Horticulture, 2019)
Ten onion and two garlic varieties have been released. Among these, red onion varieties, viz. Bhima Super, Bhima Red, Bhima Dark Red and white bulb varieties, Bhima Shubhra and Bhima Safed are suitable for kharif season, whereas Bhima Raj (dark red), Bhima Shakti (red), Bhima Kiran (red), Bhima Light Red (red) and Bhima Shweta (white) are suitable for rabi season. Bhima Shakti, Bhima Super, Bhima Red, Bhima Raj and Bhima Shubhra are also suitable for late-kharif, which indicates that these varieties have wide adaptability in changing climate. Of these, seven onion varieties, viz. Bhima Super, Bhima Red, Bhima Raj, Bhima Dark Red, Bhima Kiran, Bhima Shubhra and Bhima Shweta; and one garlic variety, Bhima Omkar, have been notified by Central Varietal Release Committee.